Ambient changes exceed treatment effects on plant species abundance in global change experiments. (18th October 2018) - Langley, J. Adam; Chapman, Samantha K.; La Pierre, Kimberly J.; Avolio, Meghan; Bowman, William D.; Johnson, David S.; Isbell, Forest; Wilcox, Kevin R.; Foster, Bryan L.; Hovenden, Mark J.; Knapp, Alan K.; Koerner, Sally E.; et al.
Abstract: The responses of species to environmental changes will determine future community composition and ecosystem function. Many syntheses of global change experiments examine the magnitude of treatment effect sizes, but we lack an understanding of how plant responses to treatments compare to ongoing changes in the unmanipulated (ambient or background) system. We used a database of long‐term global change studies manipulating CO2, nutrients, water, and temperature to answer three questions: (a) How do changes in plant species abundance in ambient plots relate to those in treated plots? (b) How does the magnitude of ambient change in species‐level abundance over time relate to responsiveness to global change treatments? (c) Does the direction of species‐level responses to global change treatments differ from the direction of ambient change? We estimated temporal trends in plant abundance for 791 plant species in ambient and treated plots across 16 long‐term global change experiments yielding 2, 116 experiment–species–treatment combinations. Surprisingly, for most species (57%) the magnitude of ambient change was greater than the magnitude of treatment effects. However, the direction of ambient change, whether a species was increasing or decreasing in abundance under ambient conditions, had no bearing on the direction of treatment effects. Although ambient communities are inherently dynamic, there is now widespread evidence that anthropogenic drivers are directionally altering plant communities in many ecosystems. Thus, global change treatment effects must be interpreted in the context of plant species trajectories that are likely driven by ongoing environmental changes. Abstract : Across 16 long‐term global change experiments, we found strong patterns of change in plant species abundance in ambient plots. Experimental treatment effects were smaller than ambient change in magnitude for most species and only rarely reversed the direction of ambient change.